The influence of laser energies on the optical, structural and electrical properties of CdS nanoparticles by laser ablation in distilled water - yamamah khaled abdalaah; Olfat A. Mahmood; Suaad S. Shaker (Academic Science Journal)
Various laser energies were used to synthesize cadmium sulfide (CdS) nanoparticle nanostructures in distilled water using pulsed laser ablation. The influence of laser energies on the structural, optical, morphological, and electrical properties of CdS nanoparticles was studied using X-ray diffraction (XRD), UV–Vis spectroscopy, Field Emission Scanning Electron Microscope (FE-SEM), Energy Dispersive X-ray Spectroscopy (EDX), Fourier Transform Infrared Spectroscopy (FTIR), and Hall measurement. The XRD data indicate that synthesized CdS nanoparticles are nanocrystalline and possess a hexagonal wurtzite structure, the lattice constants of CdS nanostructures were calculated to be (a = 4.105), (c = 6.662), and c/a=1.622. The direct optical energy gap of CdS was determined to be between 2.42 and 1.71 eV, depending on the laser energy. In CdS colloidal solution, EDS results demonstrate the presence of Cd and S components. In FT-IR spectra, the Cd–S stretching frequency is detected in the wave number region below 700 cm-1. Electrical analysis revealed that the synthesized CdS nanoparticles were n-type with mobility increasing with laser energy 530, 590 mJ and decreasing with laser energy 650 mJ. The I-V characteristics of (n-CdS NPs/p-Si) displays that the current increased exponentially with increasing voltage, whereas at reverse bias, the current increased slowly with increasing voltage